A Legal Perspective: Implementing an Electronic Notarization System in Indonesia in the Post-Pandemic Era - Alkatiri, Naurah Humam; Putra, Mohamad Fajri Mekka; Ongko, Kyle (Jambura Law Review, 2023)
This study analyses the importance of implementing a cyber notary system in the post-pandemic digital era in Indonesia. Despite facing the possibility of another viral pandemic similar to COVID-19, Indonesia has yet to adopt the legal concept of electronic notarization. To address this issue, this study employs statutory and comparative methodologies to analyze the implementation of laws and regulations regarding electronic notarization in various foreign countries. Social distancing regulations and stay-at-home orders implemented in response to the COVID-19 pandemic made it difficult to conduct certain in-person activities; therefore, there is a need for alternative methods that notaries publics and land deed official can use to verify the authenticity of deeds and other documents. In this context, there is an acute need to introduce legal regulation regarding electronic notarization in post-pandemic Indonesia. Electronic notarization provides various benefits, such as increased convenience, enhanced security, improved efficiency, and reduced costs. A cyber notary system would enable individuals to notarize documents remotely, eliminating the need for in-person interactions, which have become difficult during the COVID-19 pandemic. Other countries, such as the United States, Japan, and the Netherlands, have already recognized the importance of electronic notarization and have established legal frameworks to enable remote notarization. For instance, the United States has passed laws and issued regulations that authorize remote online notarization, while Japan has established an electronic notarization system. The Netherlands also passed a regulation enabling electronic notarization in 2013 known as the Electronic Identification and Trust Services Regulation.